2015
DOI: 10.1007/s10266-015-0212-7
|View full text |Cite
|
Sign up to set email alerts
|

Silorane, ormocer, methacrylate and compomer long-term staining susceptibility using ΔE and ΔE 00 colour-difference formulas

Abstract: The aim of this study was to evaluate the staining susceptibility of a silorane (Filtek Silorane), an ormocer (Ceram X Duo), a methacrylate (Tetric EvoCeram) and a compomer (Dyract) exposed on the long term to various staining agents by using ΔE and ΔE 00 colour-difference formulas. Thirty-six disc-shaped specimens were made of each of the four chemically different materials, randomly divided in six groups (n = 6) and immersed in five staining solutions (red wine, juice, coke, tea and coffee) or stored dry (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…The authors found that the ormocer‐based material had a strong discoloration potential as indicated by the Δ E (8.99) values of distilled water storage. Ardu et al and Gregor et al found that the ormocer‐based composites they used in their studies showed statistically higher discoloration than the conventional restorative materials, in latter study emphasized that the insufficient integration between the resin matrix with siloxane particles and the prepolymerized microfill particles could explain the discoloration. Even if the structure of the ormocer‐base matrix is not hydrophilic, water and colorant fluids can be diffused into the composite resin and can cause discoloration susceptibility when the inorganic and organic contents are not silanized as required and the integration in the resin matrix is not sufficient …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The authors found that the ormocer‐based material had a strong discoloration potential as indicated by the Δ E (8.99) values of distilled water storage. Ardu et al and Gregor et al found that the ormocer‐based composites they used in their studies showed statistically higher discoloration than the conventional restorative materials, in latter study emphasized that the insufficient integration between the resin matrix with siloxane particles and the prepolymerized microfill particles could explain the discoloration. Even if the structure of the ormocer‐base matrix is not hydrophilic, water and colorant fluids can be diffused into the composite resin and can cause discoloration susceptibility when the inorganic and organic contents are not silanized as required and the integration in the resin matrix is not sufficient …”
Section: Discussionmentioning
confidence: 94%
“…Even if the structure of the ormocer-base matrix is not hydrophilic, water and colorant fluids can be diffused into the composite resin and can cause discoloration susceptibility when the inorganic and organic contents are not silanized as required and the integration in the resin matrix is not sufficient. 29 Many studies reported that red wine has an impact on color change for composite resins, similar to the result of this study. 11,13,14,30 Tsitrou et al 31 showed that ethanol has a solvent effect on monomers in different composites resins.…”
Section: Re S U Lt Smentioning
confidence: 99%
“…Applying the criterion of the present review, decreases in TP were perceivable after methylene blue staining (ΔTP > 2). Staining susceptibility of silorane, ormocer, methacrylate and compomer exposed on the long term (99 days) to various staining agents (red wine, juice, coke, tea, and coffee) was determined 33. As results, changes in TP varied from 0.3 (air control) to 21.1 (juice).…”
Section: Reviewmentioning
confidence: 99%
“…The three‐dimensional color measurement formulas CIEL * a * b * and CIE2000 are recommended by ISO for calculating color differences. Gregor et al reached the same statistical conclusions with both of the formulas . In this study, we used the CIEL * a * b * formula.…”
Section: Discussionmentioning
confidence: 62%
“…Gregor et al reached the same statistical conclusions with both of the formulas. 35 In this study, we used the CIEL * a * b * formula. Different studies have used different threshold values, [36][37][38] and Khashayar et al investigated the thresholds of perceptibility and acceptability of color changes by evaluating color studies in the literature.…”
Section: Discussionmentioning
confidence: 99%